Han Feizi on reputation-driven disobedience: A comparative study - LIU, Antong (Institutional Knowledge at Singapore Management University, 2024)
Must absolutist states resort to intimidation and coercion to tackle subjects' disobedience driven by their pursuit of reputation? Since canonical early modern Western thinkers broached but did not solve this question, I turn to the most renowned ancient Chinese Legalist Han Feizi's understudied account of reputation for answers. Whether as a means or an end, individuals' pursuit of reputation always challenges the authority of the absolute monarchy that endeavors to centralize state power. Forcefully confronting this pursuit is the barely but only acceptable way for the state to tackle this challenge, as non-confrontational strategies favored by many Western thinkers inevitably fail due to their incompatibility with the logic of political absolutism. Thus, Han Feizi unwittingly exposes the tension between political absolutism and reputation. This exposure adds nuances to his view of human nature and helps us understand how individuals' morally ambiguous pursuit of reputation obstructs the centralization of state power.